P53 genotype-independent anticancer effects of olibanum extract and 11-keto-beta-boswellic acid on human colorectal cancer cells - Yeongju Bae; Junsik Seo; Wooyoung Jeong (Elsevier, 2024)
Background: Colorectal cancer (CRC) is the third most common cancer, and CRC-related mortality is increasing annually. A key regulator of the cell cycle and cell death, the p53 gene, is frequently found in patients with CRC as mutants. Since tumors with abnormal p53 sometimes show resistance to anticancer drugs, it is important to develop anticancer drugs according to genetic characteristics. Although evidence shows that boswellic acids (BAs) might be potential anticancer agents, the anticancer effects and mechanisms involved in their activities in CRC are unclear. Methods and Results: Here, we investigated whether olibanum (Boswellia serrata Roxb.) extract and 11-keto-β-boswellic acid exerted cytotoxic effects against p53 wildtype, p53 mutated-, and p53-deleted human CRC cell lines. Results show that 11-keto-β-boswellic acid considerably reduced cell viability and induced cell cycle arrest in HCT116, HT29, and SW1417 cells. And increase of apoptotic cell population and morphological changes in apoptotic cells induced by 11-keto-β-boswellic acid were observed. The 11-keto-β-boswellic acid mediated cell cycle arrest and apoptosis were accompanied by changes in the expression of factors linked to apoptosis, regardless of p53 genotype. In addition, 11-keto-β-boswellic acid-treated cells dissociated from their spheroidal structure and appeared in an irregular form. Conclusions: Although further investigations are required to fully understand the underlying mechanisms, these results may provide insight into the potential of using olibanum extract and 11-keto-β-boswellic acid as therapeutic agents, with no difference in sensitivity depending on the p53 genotype.